2021
DOI: 10.3390/vetsci8070126
|View full text |Cite
|
Sign up to set email alerts
|

Claw Characteristics of Culled Sows from Three Farrow-to-Finish Greek Farms. Part 1: Claw Length Measurements, Lesion Scores and Their Association

Abstract: The aim of the study was to investigate variations in lengths and lesions in claws of culled sows and to evaluate their association. All four feet of 185 sows from three Greek farrow-to-finish farms (Farm A: 57 sows; Farm B: 64 sows; Farm C: 64 sows) were examined for lesions and their lengths were measured. All claw lengths were lower in sows of farm C compared to those from sows of B and A. Claw lengths in sows of farm B were lower compared to those from A for all lateral toes of front feet and for all media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Lameness in sows has been associated with excessive claw growth [12,13]. Additionally, claw overgrowth was correlated with increased frequency of other claw lesions [14][15][16]. Anisodactylia was common in hyperprolific sows of modern genotypes [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lameness in sows has been associated with excessive claw growth [12,13]. Additionally, claw overgrowth was correlated with increased frequency of other claw lesions [14][15][16]. Anisodactylia was common in hyperprolific sows of modern genotypes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, claw overgrowth was correlated with increased frequency of other claw lesions [14][15][16]. Anisodactylia was common in hyperprolific sows of modern genotypes [14]. According to Anil et al [17] particular types of claw lesions were associated with a higher risk for lameness.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed data on claw length measurements and lesion scores are given in the companion study (part 1) [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our experimental approach revealed evident variations between farms in regard to hoof mechanical characteristics. The companion study (part 1) [ 25 ] showed that overgrown hooves are associated with a greater lesion score. This study demonstrated that a decline in mechanical efficiency accompanies hooves with increased heel-sole length as well as hooves with high wall lesion scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation